Government Transparency through the Creation of a Website by the Village of Sukomulyo Gresik based on WordPress - Nonni Yap; Andy Chandra Pramana; Krissantina Eferyn; Nathasya Aurelia Puspitasari; Novella Eka Pandar Az Zahra (Pascasarjana Universitas Mataram, 2025)
Transparency in governance is an important aspect in improving accountability and public trust in village administration. Sukomulyo Village in Gresik has taken a strategic step by developing a WordPress-based website a publish information and provide digital services. This study aims to describe the process of creating a village website, analyze its effectiveness in improving information transparency, and identify the benefits the community derives from it. The research method uses a qualitative descriptive approach, including observation, interviews, and document analysis. The results show that the village website can provide more open information, including financial reports, development activities, administrative services, and village news. In addition, using WordPress enables easier content management and can be handled by village officials without advanced technical expertise. The implementation of the website has been proven to increase community access to information and strengthen public participation in the village governance process. Thus, creating a WordPress-based village website is a practical step toward greater transparency and better governance.